Self-concept and conformity among adolescent male and female high school students. - Salazar, Marian G
This study was conducted to investigate the relationship between self-concept and conformity among adolescents and whether such relationship differ in terms of sex and academic year levels. A sample of 200 high school students completed the Self-Concept Scale and Peer conformity Checklist. The Pearson r as well as the fisher r to z transformation were used to analyze data. The findings revealed a negative correlation between self-concept and conformity that was significant at the .05 level. No significant difference was found in terms of sex and academic year levels.